2021
DOI: 10.3389/fpsyg.2021.695967
|View full text |Cite
|
Sign up to set email alerts
|

The Family Check-Up Online: A Telehealth Model for Delivery of Parenting Skills to High-Risk Families With Opioid Use Histories

Abstract: Growing opioid misuse in the United States has resulted in more children living with an adult with an opioid use history. Although an abundance of research has demonstrated a link between opioid misuse and negative parenting behaviors, few intervention efforts have been made to target this underserved population. The Family Check-Up (FCU) has been tested in more than 25 years of research, across multiple settings, and is an evidence-based program for reducing risk behavior, enhancing parenting skills, and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Compared to services as usual, FCU has been shown to improve irritability in toddlerhood, which mediated effects on behavioral problems at school age (Smith et al, 2019). FCU can be delivered face-to-face or via telehealth and is acceptable and effective among racially and ethnically diverse families (Smith, Knoble, et al, 2014; Stormshak et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to services as usual, FCU has been shown to improve irritability in toddlerhood, which mediated effects on behavioral problems at school age (Smith et al, 2019). FCU can be delivered face-to-face or via telehealth and is acceptable and effective among racially and ethnically diverse families (Smith, Knoble, et al, 2014; Stormshak et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In order to tailor programs to family or parent needs, it is crucial to understand the differential impact of various program formats on targeted outcomes. Over the past decade or more, research has demonstrated the effectiveness of online prevention programs as alternatives to in-person versions (e.g., Franke et al, 2020), and the COVID-19 pandemic has only underscored the urgency for research into virtual program delivery via both self-directed online and telehealth (online synchronous individual provider-delivered) formats (e.g., Stormshak et al, 2021). In the military setting, most families—particularly those in the Reserve Component (i.e., the National Guard and Reserves)—do not live in military communities and may face difficulties accessing military family resources within driving distance, underscoring the importance of testing delivery modalities for this population that do not require families to be present in person.…”
Section: The Adaptive Parenting Tools/adapt Programmentioning
confidence: 99%
“…As illustrated in Figure 2 and elaborated below, parenting interventions foster develop MH and well-being as a form of "resilience inoculation." Improving early selfregulation strengthens children's capacity to "bounce back" from stressors and function adaptively in a pro-resilience cascade-building children's frustration tolerance, perspective taking, and other skills-resulting in more rewarding experiences and family outcomes (Connell & Stormshak, 2023;Stormshak et al, 2021).…”
Section: Evidence-based Mh Prevention: Self-regulation Promotion As R...mentioning
confidence: 99%
“…EBIs strengthen child and family capabilities for adaptive and flexible interactions and constructive management of emotions and behavior, strengthening emotion socialization processes (see, e.g., Hawks et al, 2020). Caregivers acquire proactive and confident regulation-promoting parenting skills that scaffold child development of “self-regulation muscles.” As illustrated in Figure 2 and elaborated below, parenting interventions foster develop MH and well-being as a form of “resilience inoculation.” Improving early self-regulation strengthens children’s capacity to “bounce back” from stressors and function adaptively in a pro-resilience cascade—building children’s frustration tolerance, perspective taking, and other skills—resulting in more rewarding experiences and family outcomes (Connell & Stormshak, 2023; Stormshak et al, 2021).…”
Section: Evidence-based Mh Prevention: Self-regulation Promotion As R...mentioning
confidence: 99%